Enhancing patient-centric care: the role of PROMs utilizing SRS-30 in pediatric scoliosis management - Marina Rosa Filezio; Ramyn Jooma; Paul Fairie; David Parsons; Maria J. Santana (Journal of Patient-Reported Outcomes)
Abstract Background Scoliosis is defined by a curvature of the spine greater than 10 degrees. The most common type of scoliosis is called Adolescent Idiopathic Scoliosis and is found in individuals between 11 to 18 years of age. It corresponds to 90% of the cases of scoliosis in the pediatric population, with an overall prevalence of 0.47–5.2%, affecting girls more than boys (3:1). There are different treatment options for scoliosis, and surgery is reserved for patients with curves greater than 45 degrees while still growing or greater than 50 degrees for skeletally mature patients. There is a growing recognition of the important role of patient-reported outcomes measures (PROMs) for understanding the impact of scoliosis on individuals’ lives and its management. This paper explores the importance of PROMs, specifically the Scoliosis Research Society-30 (SRS-30) questionnaire, in assessing and improving the quality of care for pediatric scoliosis patients that were submitted to surgical intervention. Methodology PROMs data were collected at predefined time points: pre-operatively (baseline), and post-operatively at 3, 6, and 12 months. The evaluation encompassed 23 (pre-operative assessment) to 30 questions (follow-up) and included five key domains: Function/Activity, Pain, Self-Image/Appearance, Mental Health, and Satisfaction with Management, as well as possible changes in the results before and after surgery. Results 115 patients participated in this study, of whom 79% were females (mean age 14.5 years). Function/Activity was the only domain to exhibit a significant score decrease in the post-operative follow-up, with a return to baseline levels at the 12-months mark. All other domains showed statistically significant improvement over time, with the steepest increase observed at 3 months for Self-Image/Appearance and Satisfaction with Management. Age did not significantly influence on the results across any of the five domains. Conclusions This project highlights the pivotal role of PROMs, with a specific focus on the SRS-30 questionnaire results, in creating a more holistic and patient-centered approach to scoliosis management.